2019
DOI: 10.1128/iai.00523-18
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum Cyclic GMP-Dependent Protein Kinase Interacts with a Subunit of the Parasite Proteasome

Abstract: Malaria is caused by the protozoan parasite Plasmodium, which undergoes a complex life cycle in a human host and a mosquito vector. The parasite’s cyclic GMP (cGMP)-dependent protein kinase (PKG) is essential at multiple steps of the life cycle. Phosphoproteomic studies in Plasmodium falciparum erythrocytic stages and Plasmodium berghei ookinetes have identified proteolysis as a major biological pathway dependent on PKG activity. To further understand PKG’s mechanism of action, we screened a yeast two-hybrid l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
3
8
0
Order By: Relevance
“…URP likely regulates ubiquitination and degradation of proteins by the proteasome, and it is reported to have phosphorylation sites at position S37 and S140 ( Collins et al., 2014 , Kumar et al., 2017 ). A recent report found that PKG phosphorylates RPT1, an AAA + ATPase present in the 19S regulatory unit of the proteasome, and regulates parasite proteolysis ( Govindasamy et al., 2019 ). Interestingly, the same report highlighted the importance of proteolysis for invasion by sporozoites of hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…URP likely regulates ubiquitination and degradation of proteins by the proteasome, and it is reported to have phosphorylation sites at position S37 and S140 ( Collins et al., 2014 , Kumar et al., 2017 ). A recent report found that PKG phosphorylates RPT1, an AAA + ATPase present in the 19S regulatory unit of the proteasome, and regulates parasite proteolysis ( Govindasamy et al., 2019 ). Interestingly, the same report highlighted the importance of proteolysis for invasion by sporozoites of hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, little is known about proteins interacting with PKG in eukaryotes as few partners have been identified (13,(47)(48)(49). In Plasmodium, the only previous data available for a PKG-interacting protein came from an in vitro study using the kinase domain of PKG (50), while a putative interaction between PKG and ICM1 was detected in a very recent elegant study profiling a potent inhibitor of PKG. However, conditional knockdown of ICM1 in that work resulted only in a minor growth defect, perhaps due to the different conditional system used (51), the TetR-DOZI aptamer system, which may require more than one cycle to achieve efficient down-regulation (52).…”
Section: Discussionmentioning
confidence: 99%
“…Upstream of Ca 2+ , cyclic guanosine monophosphate (cGMP) activates protein kinase G (PKG), resulting in the release of intracellular Ca 2+ (Carey et al, 2014; Kebaier & Vanderberg, 2010; Ono et al, 2008), via the action of phosphoinositide phospholipase C (PI‐PLC) and the production of inositol triphosphate (IP3) (Carey et al, 2014). The use of PKG inhibitors and PKG mutagenesis showed that PKG is required in P. berghei for TRAP secretion, sporozoite gliding motility and host cell invasion (Govindasamy et al, 2016; Govindasamy et al, 2019; Panchal & Bhanot, 2010). Serum albumin, a natural agonist for PKG‐dependent microneme secretion (Brown et al, 2016), also activates Ca 2+ ‐dependent motility in sporozoites (Kebaier & Vanderberg, 2010).…”
Section: Signal Transduction In Plasmodium Sporozoites During Migration and Invasionmentioning
confidence: 99%